Agar-Plate Screening for Acid Dyes Decolourization by Three Strains of Pleurotus eryngii Isolated from Tunceli, Elazig and Hakkari Province of Turkey - Yildirim, N.; Yildiz, A.; Aydin, H. (Asian Journal of Chemistry, 2010)
Many synthetic dyes present in industrial wastewaters are resistant to degradation by conventional treatments. In this study, the ability to decolourize two textile dyes by Pleurotus eryngii strains collected from geographically different habitats of Turkey was evaluated on agar plates. For all strains, growth and decolourization halos were determined on malt extract agar plates containing 0.1 and 0.2 g/L of acid red 183 or acid green 25. Each P. eryngii strain showed certain decolourization capacities and was able to decolourize both acid red 183 and acid green 25 on the malt extract agar plates, but not to the same extent. Both dyes at all concentrations were found to be toxic for P. eryngii growth. The presence of the dyes in plates reduced the mycelial growth of all strains in comparison with the control culture growing in the medium without dyes. A positive correlation was found between the mycelial growth rate and the decolourization ability.